KONDISI TEMPAT KERJA BERPENGARUH TERHADAP KINERJA PEGAWAI DI KANTOR BADAN PELAYANAN TERPADU SATU PINTU DAN PENANAMAN MODAL DAERAH (BPTSPPMD) - Yuliasih, Ismayawati (PREDIKSI, 2016)
This study aims to know the influence of working conditions on the performance of employees in the office of the Agency One Stop Services and Investment Board (BPTSPPMD) East Kutai, therefore the researchers to formulate hypotheses "Allegedly factor workplace has a significant influence on employee performance office Agency One Stop Services and Investment Board (BPTSPPMD) East Kutai Regency ".The timing of the research was conducted in late December 2015 to April 2016 for 4 (four) months. The research method in this study is quantitative, the data obtained through direct observation to the field, interviews and distributing questionnaires to the interviewees by the number of samples is 19 (nineteen) of respondents.Based on Pearson correlation calculations known there is a correlation between the work environment with employee performance with the number 0,887. This figure is interpreted as a very strong correlation between workplace with employee performance.While the t test t-test produces figures, obtained t count = 7909. and t-table = 2.109. Thus the t-count larger than t-table so that H0 rejected and H1 accepted which means that the hypothesis is accepted, because there is significance (significance) between the workplace to employee performance offices of the Agency One Stop Services and Investment Board (BPTSPPMD) District East Kutai.